Kant’s Anthropology - Wilson, Holly L. (Con-Textos Kantianos. International Journal of Philosophy, 2022)
Review of Louden, Robert, Kant’s Anthropology, Cambridge, Cambridge University Press, 2021, pp. 1-53, 9781108742283.